Cuestiones de método: la problemática del ejemplo en Foucault y Agamben (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This article explores the concepts of example and paradigm in their epistemological and ethical-political dimensions, in the perspective of the Aristotelian problematic of reasoning by examples, in the researches of Michel Foucault and Giorgio Agamben. It argues that, although theirs points of contact, we find in theses authors two different archaeologies of example.